Tissue and Cell Processing : An Essential Guide - Fehily, Deirdre (Chichester, West Sussex, U.K. : Wiley-Blackwell, 2012)
"By presenting the latest technological advances and growing national and international regulation, this new book explores state-of-the-art developments in the challenging field of tissue and cell processing. It provides a guide to easier and safer practice in operational principles of preservation, decontamination, and sterilization. Nearly half of the book is devoted completely to tissue- or cell-specific issues relating to processing. With lists of learning points and case studies which consist of sample processing protocols, descriptions of where processing went wrong, sample risk assessments, or validation studies, the authors help you find specific information fast."--
10: Training of Tissue Bank Personnel11: Cardiac Tissue: Specific Recovery and Processing Issues; 12: Skin: Specific Recovery and Processing Issues; 13: Ophthalmic Tissues: Specific Recovery and Processing Issues; 14: Skeletal Tissue: Specific Recovery and Processing Issues; 15: Processing of Cells for Transplantation; 16: Gametes and Embryos: Specific Collection and Processing Issues; 17: Engineering of Human Tissue Grafts; Index; Color Plates.
Includes bibliographical references and index.
Print version record.
Keywords: Transplantation of organs, tissues, etc; Cell transplantation; Preservation of organs, tissues, etc; MEDICAL -- Surgery -- Transplant; Cell transplantation; Preservation of organs, tissues, etc; Transplantation of organs, tissues, etc; Electronic books; Electronic books